Beyond adjustment : the Asian experience - Streeten, Paul; International Monetary Fund; Indian Council for Researh on International Economic Relations (Washington : International Monetary Fund, 1988)
This book, edited by Paul Streeten, examines the ends and means of adjustment, aspects of trade policy, and lessons from the experience of South and East Asia, as well as comparing the debt situations of Asian and Latin American countries.
Proceedings of a conference sponsored by the Indian Council for Research on International Economic Relations and the International Monetary Fund.
Includes bibliographies
occ 16/2019
Loans
Keywords: Economic stabilization; Economic policy; International economic relations; Foreign economic relations; Asia